2018
DOI: 10.1111/1467-8462.12269
|View full text |Cite
|
Sign up to set email alerts
|

Work Me Not Into Temptation: Exploring the Relationship between Work and Healthy Eating in Dieters Using Data from the HILDA Survey

Abstract: We explore if competing demands measured in terms of market and non-market activities impact on dieters' resolve to eat healthily. The analysis uses data from 2007 and 2009 of the Household Income and Labour Dynamics of Australia (HILDA) survey. The estimation strategy employs a random effects maximum likelihood estimator. For women, being unemployed is negatively associated with healthy eating whereas having young children is positively associated with healthy eating. For both genders, being divorced is negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Another study found no association between work hours and commute time with diet quality among dieters in Australia 31. That study only considered work hours and commute time separately and used hourly wage as a proxy for work hours,31 so any conclusions drawn from this analysis need to be interpreted cautiously, since its measure of work hours reflects income rather than hours worked.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another study found no association between work hours and commute time with diet quality among dieters in Australia 31. That study only considered work hours and commute time separately and used hourly wage as a proxy for work hours,31 so any conclusions drawn from this analysis need to be interpreted cautiously, since its measure of work hours reflects income rather than hours worked.…”
Section: Introductionmentioning
confidence: 97%
“…Very few prior studies have explored associations between work hours and commute time with food practices in Australia 30 31. One study suggested minimal differences in dietary intakes between women living with children working different hours, with findings indicating greater alcohol and caffeine intake but no differences in intake of most nutrients when comparing those working 25 hours or more per week to those working less hours or not working 30.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation